Determination and Statistical Analysis of Effective Watermarking Application among Varied Medical Images - Ayuba, Shehu; Usman, Babawuro (IJRDO -Journal of Computer Science Engineering, 2016)
As security is very crucial in almost every sector of services nowadays, watermarking is more or less an important mechanism in securing vital information such as medical images. Water marking aimed at providing secure medical images through integrity verification, such that unauthorized person cannot be able to modify it. In a bid to find a secured watermarking technique which prevents a medical image from degradation, this research explores a mechanism known as Hybrid Transformed Watermarking. Two mechanisms are employed that include Discreet Cosine Transform (DCT) and Discreet Wavelet Transform (DWT). The two techniques were combined to transform a medical image with the intent of providing authenticity and integrity verification, the final result was an efficient watermarked imaged.